A retrospective study of the relationship between the pathologic subtype and lymph node metastasis of lung adenocarcinomas of ⩽3 cm diameter. Issue 36 (4th September 2020) - Lin, Wenwei; Huang, Mingcheng; Zhang, Zhenyang; Chai, Tianci; Chen, Sui; Gao, Lei; Lin, Jiangbo; Kang, Mingqiang
Abstract : Abstract: To analyze the relationship between pathologic subtype and lymph node metastasis for lung adenocarcinomas of ⩽3 cm diameter. We retrospectively studied 384 patients with operable lung adenocarcinomas of ⩽3 cm diameter that had been radically resected by lobectomy or anatomic segmentectomy with systematic nodal dissection, at the Fujian Medical University Union Hospital between March 2014 and March 2016. Lymph node metastasis pN1 + pN2 (pN+) was found in 2 of 104 (1.9%) patients with tumor diameter ⩽1.0 cm, 12 of 159 (7.5%) patients with tumor diameter >1.0 cm but ⩽2.0 cm, and 35 of 121 (28.9%) patients with tumor size >2.0 cm but ⩽3.0 cm ( P < .01). Lymph node metastasis pN+ was found in 19 of 53 (35.8%) patients with visceral invasion pleural (VIP) and 30 of 331 (9.0%) patients without VIP ( P < .05). It was also found in 16 of 51 (31.3%) patients with high serum CEA concentrations and 28 of 297 (9.4%) patients with normal concentrations ( P < .05). In a multivariate analysis, tumor diameter, VIP, high serum CEA concentration, and pathologic subtype were significant risk factors. The prevalences of lymph node metastasis pN+ were: 0.0% (0/2), 0.0% (0/89), 3.2% (1/31), 16.2% (34/209), 7.7% (1/13), 46.7% (7/15), 100% (4/4), and 11.8% (2/17) for adenocarcinoma in situ (AIS); minimally invasive adenocarcinoma (MIA); predominantly lepidic (LEP), acinar (ACI), papillary, solid (SOL), and micropapillary (MIP) tumors; and variants of invasive adenocarcinoma, respectively ( P < .05). For predominant SOL and MIP tumors, the prevalences of lymph node involvement were significantly higher than for the other subtypes. We have shown that lymph node metastasis in patients with tumor diameter ⩽3 cm differs according to lung adenocarcinoma subtype. AIS and MIA were not associated with lymph node metastasis; therefore, systematic nodal dissection may be unnecessary. The prevalence of lymph node metastasis rate was low for LEP, suggesting that systemic lymph node sampling is sufficient. In contrast, for other pathologic subtypes, including SOL and MIP, systematic lymph node dissection should be performed.